APPROACHES TO DEVELOPMENT OF SOLID- SELF MICRON EMULSIFYING DRUG DELIVERY SYSTEM: FORMULATION TECHNIQUES AND DOSAGE FORMS – A REVIEW - Sharma, Shobhit; Khinch, M. P.; Sharma, Natasha; Agrawal, Dilip; Gupta, M. K. (Asian Journal of Pharmaceutical Research and Development, 2013)
Oral route still remains the favorite route of drug administration in many diseases and till today it is the first way investigated in the development of new dosage forms. The major problem in oral drug formulations is low and erratic bioavailability, which mainly results from poor aqueous solubility. Solubility is one of the most important parameter to achieve desired concentration of drug in systemic circulation for therapeutic response. As a consequence of modern drug discovery techniques, there has been a steady increase in the number of new pharmacologically active lipophilic compounds that are poorly water soluble. It is a great challenge for pharmaceutical scientist to convert those molecules into orally administered formulation with sufficient bioavailability. Among the several approaches to improve oral bioavailability of these molecules, Self- micron emulsifying drug delivery system (SMEDDS) is one of the approaches usually used to improve the bioavailability of hydrophobic drugs. However, Conventional SMEDDS are mostly prepared in a liquid form, which can have some disadvantages. Accordingly, solid SMEDDS (S-SMEDDS) prepared by solidification of liquid/semisolid selfmicron emulsifying (SME) ingredients into powders, have gained popularity. This article gives an overview of the recent advancements in S-SMEDDS such as development methods and the future research direction